2021
DOI: 10.5194/jbji-6-337-2021
|View full text |Cite
|
Sign up to set email alerts
|

Cost of off-label antibiotic therapy for bone and joint infections: a 6-year prospective monocentric observational cohort study in a referral centre for management of complex osteo-articular infections

Abstract: Abstract. Introduction: Costs related to bone and joint infection (BJI) management are increasing worldwide, particularly due to the growing use of off-label antibiotics that are expensive treatments (ETs), in conjunction with increasing incidence of multi-drug-resistant pathogens. The aim of this study was to evaluate the whole costs related to these treatments during the patient route, including those attributed to the rehabilitation centre (RC) stay in one regional referral centre in France. The total annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The increase along the period of study of linezolid and daptomycin consumption, both antibiotics indicated for the treatment of Gram-positive microorganism infections, more frequent in this ICU, may be due to the introduction of the generic drug products in the therapeutic guide of the hospital, linezolid in 2015 and daptomycin in 2018. The increase of prescription of these antibiotics after generic approval is also reported in other studies [ 30 ]. In a recent study [ 6 ], overall total daily defined doses for each antibiotic class were not significantly different between SDD and standard of care.…”
Section: Discussionsupporting
confidence: 78%
“…The increase along the period of study of linezolid and daptomycin consumption, both antibiotics indicated for the treatment of Gram-positive microorganism infections, more frequent in this ICU, may be due to the introduction of the generic drug products in the therapeutic guide of the hospital, linezolid in 2015 and daptomycin in 2018. The increase of prescription of these antibiotics after generic approval is also reported in other studies [ 30 ]. In a recent study [ 6 ], overall total daily defined doses for each antibiotic class were not significantly different between SDD and standard of care.…”
Section: Discussionsupporting
confidence: 78%
“…5,6 Although linezolid first became commercially available in 2000, its use has increased exponentially because of extensive on- and off-label use, and the recent availability of several generic formulations that have substantially reduced the cost of the drug. 7–9…”
Section: A Brief Introduction To Linezolid An Increasingly Important ...mentioning
confidence: 99%
“…5,6 Although linezolid first became commercially available in 2000, its use has increased exponentially because of extensive on-and offlabel use, and the recent availability of several generic formulations that have substantially reduced the cost of the drug. [7][8][9] The PI for linezolid (Xyvox, Zyvoxid, Pfizer) states that a '1 size fits all' convenient dosing regimen of 600 mg twice daily is appropriate for all adult patients regardless of weight, body mass index, age, presence of sepsis, and renal or hepatic function. 10 The PI also stated that the total treatment duration should not exceed 28 days because of the increased risk of toxicity, particularly myelosuppression and neuropathy.…”
Section: A Brief Introduction To Linezolid An Increasingly Important ...mentioning
confidence: 99%